Online Peer-to-Peer (P2P) Lending : A Systematic Literature Review Using Bibliometric Analysis - Kumari, Sarasanabelli Prasanna; Mohanty, Madhusmita (Prabandhan: Indian Journal of Management, 2024)
Purpose : The purpose of this bibliometric analysis was to find out the peer-to-peer lending platforms trend published from 2010 to 2024. The data was collected from Scopus and the Web of Science database. The present study aimed to uncover research areas of focus, leading authors, journal categories, and country affiliations in the area of peer-to-peer lending. Design/Methodology/Approach : The investigation, which included estimations of nation affiliation, journal classification, author productivity assessment, and extensive keyword research, was conducted using R programming. Over the 15 years, a total of 1,401 publications were reviewed and categorized in order to find patterns and trends. Findings : The study revealed that there were a considerable number of articles from China. It was also evident that most are consistent with P2P lending research. The central themes of the present study involved crowdfunding, fintech, credit scoring, and artificial intelligence. Remarkably, the Finance Research Letters journal appeared to be the best in the area, and LIU Y was named as the most renowned author. Practical Implications : The outcome could be compared to financial technology policymakers’ and researchers’ decisions to guide policy and research topics. By understanding worldwide trends and academic collaboration in peer-to-peer lending research, we can make decisions and improvise the field with ample depth evidence. Originality/Value : This study thus completed the ongoing search for information and understanding about the innovative settings of peer-to-peer lending in the fields of academia, finance, and technology. Identification of key research trends, prominent contributors, and policy trends enables the survey to provide insightful data for future research.